Implementasi Model Asset Based Community Development (ABCD) dalam Pendampingan Pemenuhan Kompetensi Leadership Pengurus MWC NU Adimulyo - Atim Rinawati; Atik Faizul H; Umi Arifah (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2022)
This service activity aims to provide assistance in fulfilling the leadership competencies of MWC NU Adimulyo management, as well as carry out institutional self-evaluations related to fulfilling leadership competencies. In implementing this community service, the Assest Based Community Development (ABCD) method is used with 5 (five) stages of activity, namely discovery, dream, design, define, and destiny. The results of this activity were (1) The five stages were carried out through coordination and collaboration between students and MWC NU Adimulyo management under the guidance of Field Supervisors (DPL) (2) Community service activities resulted in improvements in fulfilling 4 (four) indicators of leadership competency assessment, namely preparation MWC NU conference, management recruitment mechanisms, leader competencies, and leadership strategies. Based on the institution's self-evaluation conducted, the leadership competence of MWC NU Adimulyo management was in the very good category with a score of 12.